Rational Addiction with Learning and Regret - Orphanides, Athanasios; Zervos, David (Journal of Political Economy, 1995)
We present a theory of rational behavior in which individuals maximize a set of stable preferences over goods with unknown addictive power. The theory is based on three fundamental postulates: that consumption of the addictive good is not equally harmful to all, that individuals possess subjective beliefs concerning this harm, and that beliefs are optimally undated with information gained through consumption. Although individual actions are optimal and dynamically consistent, addicts regret their past consumption decisions and regret their initial assessment of the potential harm of the good. Addict-prone individuals who believe "it could not happen to them" are most likely to be drawn into a harmful addiction.